Der AEG-Streik in Nürnberg: fast ein Erfolg - Artus, Ingrid (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2006)
The AEG-strike: nearly a success. The workers of the AEG-factory in Nuremberg striked during 43 days against the delocalisation of the production to Eastern Europe. The strike was supported by an amazing regional, national and international solidarity. In the end, the union agreed to a compromise, obtaining relativly high payments of damages, but consenting in the closure of the plant. The article retraces the development of the conflict, analyses the ‘resources of solidarity’ and tries to evaluate its outcome and the underlying union strategies.